Revealing the oceanic spawning migrations of Australian long-finned eels (Anguilla reinhardtii) via satellite telemetry - Koster, Wayne M.; Westerberg, Håkan; Dawson, David; Kahsnitz, Roland; Aarestrup, Kim; Fanson, Ben (Frontiers in Marine Science, 2025)
This study presents the first investigation into the oceanic spawning migrations of Australian long-finned eels (Anguilla reinhardtii), a critical and previously undocumented stage in their life cycle. In autumn 2024, twenty adult eels were collected from two estuaries in southern Australia and tagged with pop-up satellite archival tags. Individuals were successfully tracked up to five months, with some migrating as far as 2,500 km from their release sites to the tropical Coral Sea. Migration trajectories revealed relatively consistent and direct movement pathways, with eels remaining several hundred kilometers offshore for much of their journey before venturing farther offshore during later stages. Tag data provided clear evidence of predation events, indicating that escapement to the sea does not guarantee successful spawning and highlighting the potential ecological role of eels within marine food webs. Approximately 40% of migrations were prematurely terminated due to predation, with sharks likely responsible in nearshore environments and marine mammals in offshore regions. Additionally, consistent observations of diel vertical migration, characterized by nocturnal ascents toward the surface and diurnal descents to deeper waters, offer valuable insights into behavioral adaptations during the oceanic migration phase of this enigmatic life history. Tag endpoints and reconstructed migratory trajectories generally aligned with a region between the East Australian Current and the Lord Howe Seamount Chain. Several endpoints clustered within a small region of the northeastern Coral Sea, south of the Solomon Islands. These locations align with historical leptocephali collection sites, strengthening the hypothesis that the spawning area of long-finned eels lies in the northeastern Coral Sea.